The mediating effect of consumers' price level perception and emotions towards supermarkets - A. Celil Cakici; Sena Tekeli (European Journal of Management and Business Economics (EJM&BE), 2022)
Purpose - This study aims to reveal the impact of consumers' price sensitivity on their purchase intention within the scope of supermarkets. Besides, the study aims to examine the impact of consumers' price sensitivity on their price perception level and emotions and the impact of consumers' price level perception and emotions toward supermarkets on their purchase intention. It also aims to detect the mediating effects of consumers' price level perception and emotions toward supermarkets between their price sensitivity and purchase intention. Design/methodology/approach - The quota sampling method was used to form the study sample. The population was 20-69-year-old consumers. The study sample included 513 consumers, 276 of whom were men, and 237 of whom were women. Data were collected via a questionnaire by the researchers in Mersin's (Turkey) five central counties. Explanatory and confirmatory factor analyses and structural equation models were used to analyze data. Findings - Consumers' price sensitivity, perception of cheapness, perception of expensiveness and positive emotions toward supermarkets affect their purchase intention. Besides, price sensitivity affects their perception of cheapness while it does not affect their perception of expensiveness. It influences negative emotions, but not on positive emotions. Consumers' perception of cheapness and perception of expensiveness have impacts on positive emotions toward supermarkets. It was additionally discovered that perception of cheapness and perception of expensiveness affected negative emotions toward supermarkets. A contributed finding was that perception of cheapness had a partial mediating role between price sensitivity and purchase intention. Practical implications - The study provides managerial implications in terms of understanding consumers' behavioral changes, developing effective pricing strategies and achieving competitive advantages over the other retailing companies. Originality/value - The study illustrates that consumer behavior can be explained by a theoretical construct considering the price perception levels and emotions toward supermarkets in examining the effect of consumers' price sensitivity on their purchase intention. Therefore, it contributes to explain consumers' behavior by bringing the stimulus-organism-response (SOR) model into a theoretical construct.
Keywords: 650; Emotion toward supermarkets; Price level perception; Price sensitivity; Purchase intention